Too hot to handle? the greenhouse effect - Gribbin, Mary; Gribbin, Mary; Riley, Jon (London Transworld Publishers Ltd., 1992)
Looks at the causes and threats of the growing greenhouse effect and suggests steps which individuals and governments can take to address the problem.
"A Corgi book"
Includes bibliographical references (pages 92-93) and index.
Keywords: Greenhouse effect, Atmospheric -- Juvenile literature